Immunohistochemical and Fluorescence In Situ Hybridization Analysis of MYC in a Series of 17 Cutaneous Angiosarcomas: A Single-Center Study. (May 2018) - Requena, Celia; Rubio, Luis; Lavernia, Javier; Machado, Isidro; Llombart, Beatriz; Sanmartín, Onofre; Traves, Víctor; Guillén, Carlos; Cruz, Julia
Abstract : Abstract: Cutaneous angiosarcoma (AS) is an uncommon, aggressive sarcoma whose incidence is rising because of the increasing use of radiation therapy, especially in breast cancer. The few studies on the relevance of prognostic factors, such as MYC status in cutaneous AS, have reported inconclusive findings, with some authors reporting MYC amplification only in postirradiation and lymphedema-associated AS and others reporting evidence of MYC amplification in idiopathic AS. We analyzed 17 cases of cutaneous AS (6 idiopathic AS, 10 postirradiation AS, and 1 lymphedema-associated AS) treated at our institute between 2000 and 2015. Follow-up data were available in all cases. We compared the presence/absence of MYC amplification by fluorescence in situ hybridization (FISH) and immunohistochemical (IHC) MYC overexpression in the different AS subtypes. We also investigated potential associations between MYC amplification and prognosis. MYC amplification was observed by FISH in 6 of 14 informative cases. The positive cases were all secondary AS (5 postirradiation AS and 1 lymphedema-associated AS). IHC detected MYC overexpression in 8 of 15 informative cases (7 secondary AS and 1 idiopathic AS). In conclusion, MYC amplification and MYC overexpression were detected almost exclusively in secondary AS. No associations were found between MYC amplification/overexpression and prognosis. We found MYC amplification or overexpression in a similar proportion of the patients who died and who were still alive at the end of the study. In the group of 9 patients who died, MYC was detected by FISH in 4 cases and by IHC in 5. The corresponding figures in the group of 6 patients still alive were 2 by FISH and 3 by IHC.